2012
DOI: 10.1186/1742-4690-9-13
|View full text |Cite
|
Sign up to set email alerts
|

Spt6 levels are modulated by PAAF1 and proteasome to regulate the HIV-1 LTR

Abstract: BackgroundTat-mediated activation of the HIV-1 promoter depends upon a proteasome-associated factor, PAAF1, which dissociates 26S proteasome to produce 19S RP that is essential for transcriptional elongation. The effect of PAAF1 on proteasome activity could also potentially shield certain factors from proteolysis, which may be implicated in the transcriptional co-activator activity of PAAF1 towards the LTR.ResultsHere, we show that Spt6 is targeted by proteasome in the absence of PAAF1. PAAF1 interacts with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
(71 reference statements)
2
14
0
Order By: Relevance
“…Target sequences are shown in Extended Experimental Procedures. PCR primer sequences to amplify TAR, early, luc (coding region), luc 3′, and GAPDH-Q have been described elsewhere (Nakamura et al, 2012). Sequences of additional oligonucleotide pairs used are shown in Extended Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Target sequences are shown in Extended Experimental Procedures. PCR primer sequences to amplify TAR, early, luc (coding region), luc 3′, and GAPDH-Q have been described elsewhere (Nakamura et al, 2012). Sequences of additional oligonucleotide pairs used are shown in Extended Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…This study and others aimed at understanding the basic mechanisms of Pol I activity are crucial to provide a framework for future therapies. Spt6 is conserved between yeast and humans, and knockdown of hSpt6 alters the expression of many tumor suppressor and proto-oncogenes (75). Interestingly, hSpt6 has also been shown to physically interact with SIRT7 (76), which in turn binds Pol I.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the base, base-like complex, and RP function in transcription, independent of the proteolytic function of the proteasome, implying that the proteasome subcomplexes may have specific roles in cells [43][44][45] . However, our results suggest that the 26S proteasome is a very stable complex, and that free base, RP, and subunits are not present at detectable levels anywhere in the cell, at least under normal culture conditions.…”
Section: Discussionmentioning
confidence: 99%